2020
DOI: 10.1002/anie.202003079
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Transformations with Iodine Azide after Release from an Ion‐Exchange Resin

Abstract: This report discloses the photochemical homolytic cleavage of iodine azide after its formation following release from polymer‐bound bisazido iodate(I) anions. A series of radical reactions are reported including the 1,2‐functionlization of alkenes and the unprecedented chemoselective oxidation of secondary alcohols in the presence of primary alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…However, the intermediate C-radical formed can be trapped with TEMPO to furnish the anti-azido-oxygenated product. 1 Sterically demanding alkenes preferentially still furnish 1,2-bisazides under these conditions. V. George, A. Kirschning…”
Section: C)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the intermediate C-radical formed can be trapped with TEMPO to furnish the anti-azido-oxygenated product. 1 Sterically demanding alkenes preferentially still furnish 1,2-bisazides under these conditions. V. George, A. Kirschning…”
Section: C)mentioning
confidence: 99%
“…While haloazides like iodine azide have been known for many years, their use in synthetic organic chemistry has been considered challenging due to their unstable or even explosive nature. 1 Due to the extraordinary versatility of these interhalogen reagents for synthetic chemistry, there is a fundamental demand for safe and easy-to-use substitutes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Filtered polymeric by-products such as 4 can be used to recover the iodide loaded exchange resin 1 from where polymer-bound reagent 3 can be regenerated. 1,2 It has been suggested that iodine azide is released into solution from the polymer-bound bisazido iodate (I) complex 1 into the organic solvent of choice. There it can undergo a variety of reactions under well controlled conditions.…”
mentioning
confidence: 99%
“…However, if the mixture is heated instead of being exposed to irradiation, the Curtius rearrangement takes place forming the carbamoyl azide. 1,6,7 Accepted Manuscript…”
mentioning
confidence: 99%